Regulation of cys-based protein tyrosine phosphatases via reactive oxygen and nitrogen species in mast cells and basophils - Heneberg, P; Dráber, P (Current medicinal chemistry, 2005)
Activation of mast cells and basophils is accompanied by the production of reactive oxygen and nitrogen species that regulate diverse signaling pathways leading to the release of inflammatory mediators and production of a variety of cytokines. Although the functional pathways of reactive oxygen and nitrogen species in vivo are not completely understood, some novel metabolic pathways can be envisioned based on recent findings that protein tyrosine phosphatases can be regulated by reversible oxidation. In this review, we describe major sources and targets of reactive oxide and nitrogen species in mast cells and basophils. Direct and indirect regulations of class I and II Cys-based protein tyrosine phosphatases (LMW-PTP, PTEN, PTP-PEST, SHP-2, PTP1B, PTPalpha, PTPepsilon, DEP-1, TC45, SHP-1, HePTP and LAR) are discussed. The combined data highlight the role of redox-regulated protein tyrosine phosphatases as targets in the development of new ways of therapeutic intervention in allergies and inflammatory diseases.
Keywords: cystein; Basophils; Reactive Oxygen Species; reaktivní formy kyslíku; Mast Cells; Animals; tyrosinfosfatasy; lidé; Protein Tyrosine Phosphatases; bazofily; Cysteine; Humans; zvířata; mastocyty; Reactive Nitrogen Species; reaktivní formy dusíku